Securitization, racial cleansing, and disaster capitalism: Neoliberal disaster governance in the US Gulf Coast and Haiti. (November 2017) - Pyles, Loretta; Svistova, Juliana; Ahn, Suran
Through a critical discourse analysis of news media after the US Gulf Coast hurricane Katrina and the Haiti earthquake disasters, we draw from Soss et al.'s (2011) ideas about US poverty governance – neoliberal paternalism – to identify how a similar phenomenon of 'neoliberal disaster governance' (NDG) operates in these contexts. NDG is a set of discourses, policies, and practices, we argue, which endeavors to control disaster survivors in order to further the ends of neoliberal capitalism. Specifically, we find several key story lines that legitimate and perpetuate NDG, namely disaster capitalism, securitization and militarization of disaster settings, discourses of racial cleansing, and displacement.